The development of website-based electronic teaching materials on central tendency materials to support online learning - Putri, Yasna Kartika; Lestyanto, Latifah Mustofa (Universitas Islam Negeri Raden Intan Lampung, 2021)
During the implementation of online learning caused by the Covid-19 pandemic, there are some obstacles that occurred in the class. Almost 40% of students in observation class felt bored and spent more time doing assignments during online learning. Hence, to stimulate the activeness of students it is needed to develop website-based electronic teaching materials on central tendency material which has valid, practice, and effective criteria and can support online learning. The development model used is the 3-stage Plomp Model, namely (1) preliminary research, (2) development or prototyping phase, (3) assessment phase. The subjects of this study are 30 students in the 8H class of Junior High School 8 Malang. The results of the validation test show that the product is valid based on the validation sheet by an expert validator and a practitioner validator which get an average score of 3.9. The results of the practicality test show that the product is practically based on the teacher's and the student's response questionnaire sheets which get an average score of 3.67. Besides, about 79% of students agreed that the product is interesting. The effectiveness test shows that the product is effective since 86.7% of students met the minimum KKM score in the evaluation test. So, it could be concluded that the product developed can be used to support online learning.